The bullies: understanding bullies and bullying - Lines, Dennis (Kingsley, 2008)
What is bullying? -- Bullying in nature -- The nature nurture influence on behaviour -- Who bullies? -- Interpreting bullying behaviour -- Bullying in school -- Domestic violence and bullying partners -- Bullying of children and young people -- Bullying in the workplace